2017
DOI: 10.4149/neo_2017_403
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5 inhibits invasion and promotes apoptosis in hepatocellular carcinoma associated with osmolality

Abstract: Hepatocellular carcinoma (HCC) is one of the most difficult cancer disease for diagnosis and treatment, with a low survival rate and high recurrence rate and mortality. Nuclear factor of activated T-cells 5 (NFAT5) is mediated by osmolality and proved to be a carcinogenic gene in some tumor. However in our study we considered NFAT5 as tumor suppressor of HCC. RT-qPCR was performed for NFAT5 expression in tumor tissues. NaCl was applied to make hyperosmotic treatment. We knockdowned and overexpressed NFAT5 to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Moreover, the expression of NFAT5 promotes breast cancer cells migration (Jauliac et al, 2002 ) and tumor-driven angiogenesis (Li et al, 2014 ). On the contrary, NFAT5 acts as a tumor suppressor in hepatocellular carcinoma (Qin et al, 2017 ). In this study, we found that NFAT5 was deregulated in GBM and knockdown of NFAT5 inhibited GBM cell-driven angiogenesis in in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the expression of NFAT5 promotes breast cancer cells migration (Jauliac et al, 2002 ) and tumor-driven angiogenesis (Li et al, 2014 ). On the contrary, NFAT5 acts as a tumor suppressor in hepatocellular carcinoma (Qin et al, 2017 ). In this study, we found that NFAT5 was deregulated in GBM and knockdown of NFAT5 inhibited GBM cell-driven angiogenesis in in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor nuclear factor of activated T-cells 5 (NFAT5) was originally identified for its involvement in hypertonic kidney inner medulla adaptation (Woo et al, 2002 ; Lopez-Rodriguez et al, 2004 ). Accumulated findings have indicated that the expression levels of NFAT5 were aberrant in tumors (Küper et al, 2014 ; Qin et al, 2017 ). Moreover, growing publications demonstrated its potential roles in tumor angiogenesis and pro-angiogenic factors regulation (Li et al, 2014 ; Amara et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nfat5 deficiency promoted hepatocellular carcinogenesis and metastasis [44] in one study. Another study showed that Nfat5 promoted apoptosis and inhibited invasion in hepatocellular carcinoma cell lines [45]. A further study reports that S100a4 protein promoted proliferation and migration of ccRCC cell line through NFAT5 [46].…”
Section: Discussionmentioning
confidence: 91%
“…Subsequent studies have indicated that NFAT family members are also expressed in non-immune cells and tissues, thus participating in many normal bodily processes as well as in the development of several diseases including cancer [5]. Since the first study regarding the correlation between NFAT1/5 and cancer cells was published [6], one or more members of the NFAT family have been reported to be dysregulated in numerous cancer types including hepatocellular carcinoma (HCC) [7,8], breast cancer [9,10], colorectal cancer [11,12], and lung cancer (LC) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%